Desarrollo experimental del análisis termodinámico de los procesos y parámetros asociados al motor de combustión del laboratorio de experimentos de la UAN Sede Puerto Colombia (2021)
Currently, the Laboratory of Experiments of the Antonio Nariño University (Puerto Colombia Headquarters) has an internal combustion engine which is not operational and in need of maintenance, as well as its start-up for academic, scientific and research activities. This directly impacts the results of academic experiments carried out by students who. This generates a failure for the future engineer of the Antonio Nariño University, since a Laboratory is closely related to the reproduction of engineering experience that the future graduate will face in the industry. In this sense, knowing the operation and characteristics of an internal combustion engine becomes a relevant factor in the student's training. In addition, its use constitutes a recovery of a fixed asset of the institution. In this order of ideas, this degree project proposes to recover and start this engine, evaluating the associated thermodynamic processes, implementing a gravimetric system for the measurement of specific fuel consumption, among other activities.